Public-Private Partnerships for Providing Behavioral Health Care to Veterans and Their Families - Pedersen, Eric R.; Eberhart, Nicole K.; Williams, Kayla M.; Tanielian, Terri; Epley, Caroline (RAND Corporation, 2023)
This report will help policymakers in the Department of Veterans Affairs and other federal agencies develop and foster public-private partnerships to address the behavioral health care needs of veterans and their families. The authors develop nine key components that public-private partnerships for veteran behavioral health care would likely benefit from implementing or that could be used as a guide to develop partnerships between organizations.